2016
DOI: 10.5812/iranjradiol.38542
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Manual Exam (POP-Q) with Pelvic MRI in Assessment of Anterior Pelvic Organ Prolapse

Abstract: Background: Pelvic floor dysfunction (PFD) refers to a wide range of issues that occur when muscles of the pelvic floor are weak, tight, or there is an impairment of the sacroiliac joint, lower back, coccyx, or hip joints. PFD and pelvic organ prolapse (POP) affect about 50% of women past middle age. Symptoms include pelvic pain, pressure, dyspareunia, incontinence, incomplete emptying, and gross organ protrusion. Nowadays, there are novel diagnostic tools and therapies proposed for pelvic floor weakness and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…However, in the posterior compartment, there is a weak correlation. Similar results were found in other studies in which a good correlation in the anterior compartment and a poor correlation in the posterior compartment was found [ 13 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, in the posterior compartment, there is a weak correlation. Similar results were found in other studies in which a good correlation in the anterior compartment and a poor correlation in the posterior compartment was found [ 13 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, prolapse in asymptomatic compartments that are occult on physical examination is readily illustrated on DMRD [22]. Available studies report the comparison of findings on DMRD and clinical examination in patients with POP [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size : The estimation of sample size was based on a presumed effect size of 0.3 ( 21 ), a statistical power of 95%, and a type I error of 5% using G*Power software, version 3.1.3 with the formula for calculation of sample of correlational studies. The overall proper sample size was found to be 120 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Although this system has been evaluated and validated in many studies and its effectiveness has been confirmed, it has not yet been able to achieve its success due to many factors such as fertility, difficulty and mismatch between users (low agreement coefficient) and time consumption. Based on this, the International Association of Urology designed a simpler system (simplified POP) based on the same POP-Q system ( 20 21 ). Very few previous studies evaluated the association between POP-Q and simplified POP and suggest that these tools should be evaluated in other sociocultural contexts to generalize the results ( 12 , 14 , 18 ).…”
Section: Introductionmentioning
confidence: 99%